The Role of Sirtuin-1 in the Vasculature: Focus on Aortic Aneurysm - Budbazar, Enkhjargal; Rodriguez, Francisca; Sanchez, José M.; Seta, Francesca (Frontiers in Physiology, 2020)
Sirtuin1 (SirT1) is a nicotinamide adenine dinucleotide (NAD+)-dependent deacetylase and the best characterized member of the sirtuins family in mammalians. SirT1 shuttles between the cytoplasm and the nucleus, where it deacetylates histones and non-histone proteins involved in a plethora of cellular processes, including survival, growth, metabolism, senescence and stress resistance. In this brief review, we summarize the current knowledge on the anti-oxidant, anti-inflammatory, anti-apoptotic and anti-senescence effects of SirT1 with an emphasis on vascular diseases. Specifically, we describe recent research advances on SirT1-mediated molecular mechanisms in aortic aneurysm (AA), and how these processes relate to oxidant stress and the heme-heme-oxygenase (HO) system. HO-1 and HO-2 catalyze the rate-limiting step of cellular heme degradation and, similar to SirT1, HO-1 exerts beneficial effects in the vasculature through the activation of anti-oxidant, anti-inflammatory, anti-apoptotic and anti-proliferative signaling pathways. SirT1 and HO-1 are part of an integrated system for cellular stress tolerance, and may positively interact to regulate vascular function. We further discuss sex differences in HO-1 and SirT1 activity or expression, and the potential interactions between the two proteins, in relation to the progression and severity of AA, as well as the ongoing efforts for translational applications of SirT1 activation and HO-1 induction in the treatment of cardiovascular diseases including AA.